Effects of ultrasound and ultra-high pressure pretreatments on volatile and taste compounds of vacuum-freeze dried strawberry slice. (15th April 2022) - Wang, Chao; Zhang, Lihui; Qiao, Yu; Liao, Li; Shi, Defang; Wang, Jun; Shi, Liu
Abstract: The influences of ultra-high pressure (UHP), ultrasound (US) and their combination (UHP-US) assisted vacuum-freeze drying on volatile and taste compounds of strawberry slices were analyzed by GC-MS, HS-GC-IMS, HPLC, E-tongue as well as sensory analysis. Three pretreatments of vacuum-freeze dried strawberry slices could increase the concentrations of characteristic volatile compounds (hexanoates and 2, 5-dimethyl-4-methoxy-3(2H)-furanone), especially UHP-US ( P  < 0.05) sample, the increase of compounds associated with floral, fruity and sweet notes. Meanwhile, these pretreatments would ameliorate the taste of dried strawberry slices, individual sugars (glucose and fructose) increased, while the organic acids (malic acid and citric acid) contents decreased, which was consistent with the result of E-tongue. On the other hand, the taste of US sample was better than other samples, the glucose and fructose content (sweetness) of US sample increased by 19.42%, 23.51%, respectively, whereas the malic acid content (sourness) was decreased for 5.03%. All in all, US pretreatment would help to better improve the critical flavors for vacuum-freeze dried strawberry slices. Highlights: The flavor and taste of vacuum-freeze dried strawberry slices by US, UHP and UHP-US were evaluated. Volatile compounds, especially hexanoates and furanones, have showed the higher level in US samples. US samples had higher contents of critical individual sugar, whereas lower contents of organic acids. US pretreatment improved the taste and sensory scores of dried strawberry slices. US was a potential method to improve the formation of more flavor compounds.